Budaya Kerja Toxic dan Diskriminasi: Etika SDM yang Gagal Menciptakan Lingkungan Kerja yang Adil - Firyal Fasihah; Yulistia Natasya Safitri; Adi Lukman Hakim; nuning nurna dewi (JEB17 : Jurnal Ekonomi dan Bisnis, 2026)
ABSTRACT Negative work culture and discrimination are two interrelated issues that have a significant impact on employee mental health and performance. This paper aims to explore how a lack of ethics in human resource management contributes to the rise of an unhealthy work culture, and how policies and moral norms can be used as solutions to create a just and humane work environment. This research use qualitative methods with literature analysis from various national and international publications. The result show that the ineffective application of the principles of fairness, openness, and respect for individual dignity can lead to discrimination and injustice within organizations, the sustainable application of ethics in human resource management, which includes anti-discrimination policies, empathy training, and open communication, has been proven to reduce detrimental work cultures and improve employee well-being. Therefore, strengthening human resource ethics is a strategic approach to building sustainable and socially just organizations